1993
DOI: 10.1093/bja/70.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of I.V. Induction in Children: Comparison Between Propofol and Thiopentone

Abstract: We have compared the haemodynamic responses to i.v. propofol 2.5 mg kg-1 with those to thiopentone 5.0 mg kg-1 in 41 healthy Chinese children at induction of anaesthesia. They were allocated to four groups according to their age and induction agent received: group 1 < 2 yr, propofol, n = 9; group II < 2 yr, thiopentone, n = 9; group III 2-12 yr, propofol, n = 12; group IV 2-12 yr, thiopentone, n = 11. Anaesthesia was maintained by spontaneous ventilation with 70% nitrous oxide and 0.5% halothane in oxygen. Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 27 publications
3
36
2
3
Order By: Relevance
“…However, the reduction in cardiac index is not significantly different between propofol and thiopental sodium groups [16]. In the current study, reduction of MAP was greater after the administration of propofol compared to that after the administration of thiopental sodium, although the different was not statistically significant.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, the reduction in cardiac index is not significantly different between propofol and thiopental sodium groups [16]. In the current study, reduction of MAP was greater after the administration of propofol compared to that after the administration of thiopental sodium, although the different was not statistically significant.…”
Section: Discussioncontrasting
confidence: 79%
“…When cardiovascular effects are compared between propofol and thiopental sodium, MAP has been found to be decreased greater after the administration of propofol than that after the administration of thiopental sodium [16]. However, the reduction in cardiac index is not significantly different between propofol and thiopental sodium groups [16].…”
Section: Discussionmentioning
confidence: 91%
“…However, it has drawbacks, such as a greater risk of cardiovascular effects, besides prolonged blockade 11,27,28 . Although one of the adverse effects of propofol is reduced cardiac index and systemic vascular resistance with consequent hypotension 29 , there were no signifi cant changes in the hemodynamic parameters of both groups in the present study that could have infl uenced the neuromuscular block.…”
Section: Discussioncontrasting
confidence: 55%
“…(22) Propofol is believed to cause a reduction in systolic and diastolic arterial pressures by lowering SVRI and afterload. (23) Some studies on people and animals showed that it had no influence on CI, (23)(24)(25) while in others it caused a reduction in CI. (26,27) Its haemodynamic effects depend on the speed of administration and on associated cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%